The State of the Art of Cyber-Physical System for Monitoring and Tracking in Maritime and Fisheries Sectors - Nazzla, Rauzatul; Jaya, Indra; Rahmat, Ayi; Panggabean, Donwill; Panggabean, Yuniar Endri; Handoko, Dadang (Journal of Coastal and Deep Sea, 2024)
This article presents the state of the art of research and publications regarding cyber-physical systems which include theory and working systems as well as applications in the maritime and fisheries fields. The literature collection method is based on keywords sourced from books, dissertations and theses, scientific articles, and website pages. The results presented in the form of descriptions and illustrations based on work systems that include construction, communication, computation and control. This review is important to increase a comprehensive understanding of the concept and implementation of cyber-physical systems in the maritime and fisheries sector.